An anthropological trompe l'oeil for a common world : an essay on the economy of knowledge - Jiménez, Alberto Corsín (Ethnography, theory, experiment., 2013)
Our political age is characterized by forms of description as 'big' as the world itself: talk of 'public knowledge' and 'public goods,' 'the commons' or 'global justice' create an exigency for modes of governance that leave little room for smallness itself. Rather than question the politics of adjudication between the big and the small, this book inquires instead into the cultural epistemology fueling the aggrandizement and miniaturization of description itself. Incorporating analytical frameworks from science studies, ethnography, and political and economic theory, this book charts an itiner.